CLINICAL CASE OF SUCCESSFUL SURGICAL TREATMENT OF PULMONARY EMBOLISM IN THE PATIENT WITH 11 WEEK PREGNANCY - K. Yu. Borisov; M. S. Akulenko; E. M. Antoshina; A. F. Kalugina; D. R. Abshilava; A. A. Pak; S. S. Gutnov; A. V. Piskun; A. A. Katkov; D. I. Levikov; N. I. Rusanov (Вестник анестезиологии и реаниматологии)
Pulmonary embolism in pregnant women is fairly common complication, and it remains to be the one of major causes of maternal mortality in the number of countries. The need to compare risks of the mother and child makes the search for optimal treatment tactics very complicated in this specific case. The experience of the last decades provides evidences for choosing aggressive treatment tactics, accurate diagnostics and early surgical intervention. The authors of this article describe the clinical case of successful treatment of the young woman whose pregnancy course was complicated by pulmonary embolism at the 11th week of gestation. The article describes the results of laboratory and instrumental diagnostics and anasthesiological support technique within available scope of pharmacological and technical means. Also the article reviews the literature data on this problem. The conclusion contains recommendations for intra-operative management of such patients.